Responsabilidade objetiva por dano processual - Fagundes, Cristiane Druve Tavares (2012)
The purpose of this present study is the analysis of objective hypotheses of the civil liability proceeding existing in the Code of Civil Procedure. The addressed topic is one of the most current and relevant ones, and also the least versed by Brazil s doctrine, which justifies the necessity of further clarification on the issue. The approach of this topic begins by the relevant aspects of liability and its general bias. Civil liability is a subject that concerns all branches of law, since as a rule, by generating damage to another person in the performance of any activity one will be faced with the obligation of compensation. Immediately thereafter, civil liability is analyzed when the damage is caused by procedural activity. The process, in this context, is formed solely on the means by which the loss is carried to another. Only after the referred to assumptions are set, then the hypotheses of objective liability in the Code of Civil Procedure in Brazil are analyzed. For the accomplishment of this study, the analysis of patriotic authors came together with foreigners , in a way to seek the most upgraded information on this matter. As it couldn t be otherwise, defended views have always been sought to corroborate with the jurisprudence in Brazilian courts, therefore showing relevance of the versed topic. Therefore the aim of this study is a systematization of the concerning matter to the objective liability proceeding